Unveiling the role of polyphenols in diabetic retinopathy. (October 2021) - Behl, Tapan; Kumar, Keshav; Singh, Sukhbir; Sehgal, Aayush; Sachdeva, Monika; Bhatia, Saurabh; Al-Harrasi, Ahmed; Buhas, Camelia; Teodora Judea-Pusta, Claudia; Negrut, Nicoleta; Alexandru Munteanu, Mihai; Brisc, Ciprian; et al.
Graphical abstract: Highlights: Consumption of polyphenols is inversely associated with diabetic retinopathy. Polyphenols exhibit multiple favourable therapeutic effects comprising anti-bacterial, anticancer, anti-inflammatory and antioxidant. Polyphenols regulate the metabolism of lipids and carbohydrate, hyperglycaemia, oxidative stress, insulin resistance, and inflammatory processes. It is recommended to consume polyphenols as they are considered as rich dietary supplements. Abstract: Diabetes retinopathy (DR) is the leading cause of blindness and is considered as the most ordinary microvascular complication of diabetes mellitus (DM). The current available therapies can only be effective in the progressive stages of DR and there are various clinical studies which depicts the inconclusive outcomes of these available therapies after assessing the long-term efficacy and safety of such treatments. Moreover, there is an indispensable need of a more reliable as well as potent treatment which can be considered as more efficacious treatment for the management of DR. The treatment of DR can be possible at the early stages with polyphenols which are plant derived chemical agents and can be act as an alternative to other treatments and can optimistically prevent the further evolution of disease. The present review emphasizes the role of polyphenols on cellular and molecular mechanisms altered by DR in preclinical and clinical studies.